2015
DOI: 10.7554/elife.05648
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-selective crosstalk via the NF-κB signaling system reinforces innate immune response to alleviate gut infection

Abstract: Tissue microenvironment functions as an important determinant of the inflammatory response elicited by the resident cells. Yet, the underlying molecular mechanisms remain obscure. Our systems-level analyses identified a duration code that instructs stimulus specific crosstalk between TLR4-activated canonical NF-κB pathway and lymphotoxin-β receptor (LTβR) induced non-canonical NF-κB signaling. Indeed, LTβR costimulation synergistically enhanced the late RelA/NF-κB response to TLR4 prolonging NF-κB target gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 44 publications
(79 reference statements)
4
77
0
Order By: Relevance
“…Our work provides insights into how noncanonical signaling is transduced through balancing the amounts of distinct complexes with opposing activities. Increased or reduced processing of p100 causes cancer and defects in immunity (35)(36)(37)(38)(39). In all these cases, aberrant processing could be due to the defect in competition between RelB and the NIK:IKK1 complex for p100 binding as shown here.…”
Section: Discussionmentioning
confidence: 94%
“…Our work provides insights into how noncanonical signaling is transduced through balancing the amounts of distinct complexes with opposing activities. Increased or reduced processing of p100 causes cancer and defects in immunity (35)(36)(37)(38)(39). In all these cases, aberrant processing could be due to the defect in competition between RelB and the NIK:IKK1 complex for p100 binding as shown here.…”
Section: Discussionmentioning
confidence: 94%
“…Further stochastic simulation of the delayed differential equations can recapitulate most experimental observations (Sun and Cui, 2014). This is reminiscent of the role of p100 in connecting canonical and non-canonical NF-kB signaling (Banoth et al, 2015). Noncanonical NF-kB pathway activation not only neutralized the inhibition of p100 but also produced RelA:p52/NF-kB activity (Banoth et al, 2015).…”
Section: Models For Bimodal P53 Dynamicsmentioning
confidence: 88%
“…This is reminiscent of the role of p100 in connecting canonical and non-canonical NF-kB signaling (Banoth et al, 2015). Noncanonical NF-kB pathway activation not only neutralized the inhibition of p100 but also produced RelA:p52/NF-kB activity (Banoth et al, 2015). Chen et al, however, constructed another scenario where mono-and poly-ubiquitinated p53 were both considered .…”
Section: Models For Bimodal P53 Dynamicsmentioning
confidence: 97%
“…With the use of reciprocal bone marrow transfer experiments, Nfkb2 Ϫ/Ϫ mice given wild-type mouse bone marrow lost weight and had 100% mortality before day 10, whereas wild-type mice given either wild-type or Nfkb2 Ϫ/Ϫ bone marrow did not lose weight or show increased mortality. These findings indicate that NF-B2 expression within the nonmyeloid compartment is involved in limiting the severity of C. rodentium-associated colitis (10).…”
Section: Alternative Pathway Nf-b Signaling In Conditions Of the Gastmentioning
confidence: 98%
“…Using mouse embryonic fibroblasts, they demonstrated that LT␤R prolonged the TLR4-induced RelA response by targeting newly synthesized p100 for processing to p52, allowing formation of p65(RelA)-p52(NF-B2) dimers. This led to increased expression of proinflammatory cytokines and chemokines (10). Understanding the integration of different mechanisms of NF-B activation is a key challenge for this field.…”
Section: The Alternative Nf-b Activation Pathwaymentioning
confidence: 99%